Interplay between low-energy optical phonon modes and structural transition in PrT2Zn20 (T=Ru and Ir). (18th March 2015) - Wakiya, K; Onimaru, T; Tsutsui, S; Matsumoto, K T; Nagasawa, N; Baron, A Q R; Hasegawa, T; Ogita, N; Udagawa, M; Takabatake, T
Abstract: Atomic dynamics of Pr T 2 Zn20 for T =Ru with a structural transition at T s =138 K and T =Ir without such a transition have been studied by inelastic X-ray scattering (IXS) measurements. The IXS spectra for T =Ru reveal an optical phonon excitation at 3 meV. We assign it to low-energy vibration of the Zn atom at the 16c site by taking account of the first principles calculation [Hasegawa et al. 2012 J. Phys.: Conf. Proc.391 012016]. For T =Ir, on the other hand, the optical excitation at 3 meV was not observed. The contrasting results indicate that the low-energy optical phonon mode has a role in the structural transition in PrRu2 Zn20 and isostructural La counterparts.